How does the number of chews and temperature impact the sensory properties of plant-based cheese? - Zach Adams; Brianna Power; Matthew B. McSweeney (Food Quality and Preference, 2026)

What is expected of seaweed containing products? Consumer expectations and experiences with seaweed-containing food - Brianna Power; Cayla E.J. Weiler; Zach Adams; Mackenzie Gorman; Matthew B. McSweeney (Food and Humanity, 2026)

Petrography and pore-scale assessment of CO2 mineral trapping potential of sedimentary strata beneath the lower mainland British Columbia, Canada - Paula Ramirez-Lopez; Shahin E. Dashtgard; Marc Enter; Matthew Power; Dirk Kirste; Maziyar Nazemi; Francyne Bochi do Amarante (International Journal of Greenhouse Gas Control, 2026)

Directed evolution of Gram-negative Klebsiella michiganensis M5al for desiccation tolerance and survivability of a spray-drying encapsulation process - Benjamin M. Arbaugh; Emily M. Makeev; Matthew L. Cope-Arguello; Tiffany M. Lowe-Power; Tina Jeoh (Systems Microbiology and Biomanufacturing, 2026)
Spray drying is a scalable method for producing dry microbial inoculants, but Gram-negative bacteria often exhibit poor survival under desiccation stress. We employed a directed-evolution approach to improve the survivability of diazotroph Klebsiella michiganensis M5al during spray-drying encapsulation in cross-linked alginate microcapsules (CLAMs). Wildtype K. michiganensis M5al was serially passaged through the CLAMs spray-drying process under incrementally increasing selection pressure. Viable cell density in powders improved over 1000-fold compared to baseline, reaching 3.07 × 10 10 CFU/g over the course of the directed evolution experiment. Paired trials confirmed a statistically significant increase in survival of evolved isolates relative to the parental strain (mean difference of 1.39 log 10 , P < 0.05). Whole-genome sequencing and analysis using breseq identified candidate mutations associated with desiccation tolerance, including a single point mutation in the phosphoenolpyruvate carboxylase gene ( pepC ), suggesting a potential link between central carbon metabolism and stress adaptation. These results demonstrate that genetic adaptation can rapidly enhance microbial fitness under industrial drying conditions without modifying formulation, providing a practical strategy for improving the manufacturability and deployment of Gram-negative microbial biostimulants and related products.

Does health information influence consumer perception of seaweed-containing foods? A repeated exposure study - Rachael Moss; Matthew Code; Brianna Power; Zach Adams; Mackenzie Gorman; Matthew B. McSweeney (Algal Research, 2026)

Characterization of a precipitate sludge from a sulfuric acid plant - Simon P. Michaux; Alan R. Butcher; Duncan Pirrie; Jarno Mäkinen; Mari Lundström; Petri Latostenmaa; Jesal Hirani; Nikolaos Apeiranthitis; Tero Korhonen; Matthew R. Power (Minerals Engineering, 2026)

Regional ecosystem responses to environmental drivers in cold‐water lakes evaluated using stable isotopes of salmonid fishes - Matthew R. D. Cobain; Per‐Arne Amundsen; Åge Brabrand; Pär Byström; Jan G. Davidsen; Karl Ø. Gjelland; Jennifer E. Hansen; Ingeborg P. Helland; Trygve Hesthagen; Stein I. Johnsen; Roger I. Jones; Kimmo K. Kahilainen; et al. (Limnology and Oceanography, 2026)
Diverse environmental drivers influence food web energy and nutrient flows, a key ecosystem function, yet their relative importance remains poorly known. We compiled thousands of bulk stable isotope measurements (carbon and nitrogen) of brown trout ( Salmo trutta , n = 2854) and Arctic charr ( Salvelinus alpinus , n = 3062) from 120 cold‐water lakes across northern Europe, spanning 0.02 to 1090 km 2 in size, to quantify the relative importance of nine potential drivers of energy and nutrient flows. Fish community type and individual body size matched the well‐described ecologies of the two species: charr shifted from littoral to pelagic sources with interspecific competition, and trout opportunistically increased their trophic position with piscivorous prey availability and increasing body size. The anthropogenic impacts of water‐level regulation and catchment modification were mirrored in the two species, resulting in decreased δ 13 C values, implying increased relative pelagic production in regulated lakes, and increased δ 15 N values, possibly due to increasing cross‐boundary nutrient flows. Lake size and climatic drivers (summer precipitation and winter temperature) elicited strong species‐specific changes in isotope values, suggesting that predator‐driven ecological responses can dominate over ecosystem‐wide changes in energy and nutrient flows within lake food webs. No isotopic trends were observed with catchment productivity or shoreline complexity at the regional scale, contrasting with insights from local scale studies. This spatial mismatch suggests that environmental drivers of ecosystem processes playing out at the regional scale cannot necessarily be extrapolated from localized studies, despite correlated random lake effects capturing unexplained local baseline shifts in isotopes.

Douglas-fir dominates when grown in dual species mixtures with three western conifers - Robert A. Slesak; Michelle C. Agne; Constance A. Harrington; Matthew D. Powers (Forest Ecology and Management, 2025)

Long-term effects of tree spacing during reforestation on survival and growth of three important tree species in the Pacific Northwest, USA - Robert A. Slesak; Michelle C. Agne; Constance A. Harrington; Matthew D. Powers (Forest Ecology and Management, 2025)

Urban Tree Growth and Drought Responses Show Evidence of Climate Resilience - Manuel Esperon‐Rodriguez; Matthew Brookhouse; Sally A. Power; Diego Avi; Thomas Baer; Paul D. Rymer; Mark G. Tjoelker (Global Change Biology, 2025)
Climate change has a negative impact on the vitality of forests, and drought and heatwaves are the most influential abiotic stressors that contribute to tree health decline and mortality. Urban trees are not only vulnerable to climate change, but they also face harsh environmental conditions, including the urban heat island effect, limited soil volume and water availability. Therefore, the long‐term sustainability of urban forests relies on healthy and thriving trees and the identification of species that are resilient to climate change. Thus, it is fundamental to understand how urban trees respond to environmental conditions, including climate. This study investigates how urban trees respond to both long‐term climatic conditions and episodic extreme climate events. We evaluated variation in urban tree growth across differing climates by reconstructing growth histories and developing drought response indices. We selected 10 tree species planted in seven cities distributed along temperature and precipitation gradients across the Australian continent. We determined spatial and temporal patterns of tree‐ring growth in relation to extreme climate events. We found significant differences among cities, suggesting that local environmental conditions significantly influence tree growth. While some species showed fast annual growth in cool and wet cities, other species had similar growth across all cities or even faster growth in hot and dry cities. Urban trees generally responded positively to wetter conditions during the warmest month, which might be related to longer growing seasons and water availability. We found a positive effect of extreme hot conditions on growth, suggesting that urban trees might be well adapted to warm urban environments. Species climate‐growth relationships can help guide species selection to maximize benefits delivered by urban forests and minimize environmental and socio‐economic losses under current and future climates.

Piperine’s impact on sensory perception in different food matrices (liquid and solid) - Brianna Power; Mackenzie Gorman; Allison Stright; Rachael Moss; Matthew B. McSweeney (Food and Humanity, 2025)

Chemical Composition of Secretions from Facial Glands of Captive Hoary Bat (Lasiurus cinereus) in Virginia - Kristina R. Stefaniak; Lark Kellogg; Matthew T. Close; Karen E. Powers (Journal of Chemical Ecology, 2025)
Our study represents the first known report of hoary bat ( Lasiurus cinereus ) facial gland histology and chemical characterization of facial gland secretions. While in captivity from October 2023 to February 2024, facial secretions of a male hoary bat were observed and collected. Gas chromatography-mass spectrometry (GC-MS) analysis of a methanol extraction of November 2023 samples identified 23 compounds after comparing retention times, mass spectra, and Kovats retention index. These compounds consisted of alkanes, alcohols, ketones, terpenoids, monoacylglycerols, and androgens. Of interest was the identification of five androstane derivatives, testosterone metabolites, that have not been seen previously in mammal secretions and indicate possible mating readiness. The chemical analyses from November swabs and histological examination of facial skin in February suggest that this male was actively secreting mate-signaling compounds throughout late fall and winter months. Anecdotal mating records on wintering grounds combined with this bat’s warm captive environment likely allowed for this extended mating readiness for his many months at the wildlife center.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Weathering and cementation of historic kimberlite residues from South Africa: Implications for residue stabilization and CO2 sequestration - Justin A. Lockhart; Ian M. Power; Carlos Paulo; Amanda R. Stubbs; Nina Zeyen; Sasha Wilson; Matthew Steele-MacInnis; Robert Caldwell; Chris Gunning (Science of The Total Environment, 2024)

Remagnetisation of the Caerfai Group (lower Cambrian, SW Wales) in hot geothermal fluids during Caledonian (pre-Acadian) metamorphism - Peter Turner; Rob Ixer; Duncan Pirrie; Matthew Power (Tectonophysics, 2024)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

Dominance of net autotrophy in arid landscape low relief polar lakes, Nunavut, Canada - Paola Ayala‐Borda; Matthew J. Bogard; Guillaume Grosbois; Vilmantas Prėskienis; Joseph M. Culp; Michael Power; Milla Rautio (Global Change Biology, 2024)
The Arctic is the fastest warming biome on the planet, and environmental changes are having striking effects on freshwater ecosystems that may impact the regional carbon cycle. The metabolic state of Arctic lakes is often considered net heterotrophic, due to an assumed supply of allochthonous organic matter that supports ecosystem respiration and carbon mineralization in excess of rates of primary production. However, lake metabolic patterns vary according to regional climatic characteristics, hydrological connectivity, organic matter sources and intrinsic lake properties, and the metabolism of most Arctic lakes is unknown. We sampled 35 waterbodies along a connectivity gradient from headwater to downstream lakes, on southern Victoria Island, Nunavut, in an area characterized by low precipitation, organic‐poor soils, and high evaporation rates. We evaluated whether lakes were net autotrophic or heterotrophic during the open water period using an oxygen isotopic mass balance approach. Most of the waterbodies were autotrophic and sites of net organic matter production or close to metabolic equilibrium. Autotrophy was associated with higher benthic primary production, as compared to its pelagic counterpart, due to the high irradiance reaching the bottom and efficient internal carbon and nutrient cycling. Highly connected midstream and downstream lakes showed efficient organic matter cycling, as evidenced by the strong coupling between gross primary production (GPP) and ecosystem respiration, while decoupling was observed in some headwater lakes with significantly higher GPP. The shallow nature of lakes in the flat, arid region of southern Victoria Island supports net autotrophy in most lakes during the open water season. Ongoing climate changes that lengthen the ice‐free irradiance period and increase rates of nutrient evapoconcentration may further promote net autotrophy, with uncertain long‐term effects for lake functioning.

An updated review of the post-glacial history, ecology, and diversity of Arctic char (Salvelinus alpinus) and Dolly Varden (S. malma) - Spencer Y. Weinstein; Colin P. Gallagher; Matthew C. Hale; Tracey N. Loewen; Michael Power; James D. Reist; Heidi K. Swanson (Environmental Biology of Fishes, 2024)

Dietary Habits of Hardhead (Ariopsis felis) and Gafftopsail (Bagre marinus) Catfish Revealed through DNA Barcoding of Stomach Contents - Ana R. Osowski; Matthew B. Jargowsky; Pearce T. Cooper; Sean P. Powers; J. Marcus Drymon (Fishes, 2023)
A better understanding of trophic interactions between hardhead catfish (Ariopsis felis) and gafftopsail catfish (Bagre marinus) is crucial for developing multi-species management strategies for the northern Gulf of Mexico (GOM). These two species are often aggregated in food web models; however, limited data are available to substantiate this approach. Therefore, the present study aimed to describe the dietary habits of hardhead catfish and gafftopsail catfish using analysis of stomach contents aided by DNA barcoding. Hardhead (n = 693) and gafftopsail (n = 655) catfish were sampled in the northern GOM from 2015–2019 using both fisheries-dependent and -independent techniques. The average percent number (%N), average percent mass (%M), prey specific number (%PN), prey specific mass (%PM), and prey-specific index of relative importance (%PSIRI) were computed to quantify prey species. The stomach content analysis identified distinct differences in diet between hardhead and gafftopsail catfish. Crustaceans were the most important prey for hardhead catfish, while gafftopsail catfish showed a significantly broader dietary breadth and were primarily piscivorous. Multivariate analyses indicated that the location of capture explained the greatest amount of diet variability for both species. These findings address fundamental knowledge gaps regarding the dietary habits of hardhead and gafftopsail catfish in northern GOM ecosystems.

Aquatic environmental DNA: A review of the macro-organismal biomonitoring revolution - Miwa Takahashi; Mattia Saccò; Joshua H. Kestel; Georgia Nester; Matthew A. Campbell; Mieke van der Heyde; Matthew J. Heydenrych; David J. Juszkiewicz; Paul Nevill; Kathryn L. Dawkins; Cindy Bessey; Kristen Fernandes; et al. (Science of The Total Environment, 2023)

Age, growth and diet of crevalle jack ( Caranx hippos ) in the Gulf of Mexico - Amanda E. Jefferson; Matthew B. Jargowsky; Genevieve M. Ivec; Pearce T. Cooper; Jessica L. Carroll; Carissa L. Gervasi; Jennifer S. Rehage; John F. Mareska; Sean P. Powers; J. Marcus Drymon (Fisheries Management and Ecology, 2022)
The goals of this study were to generate baseline population dynamics parameters for Gulf of Mexico crevalle jack Caranx hippos and examine the foraging habits of Mississippi and Alabama crevalle jack. Specimens were collected from Mississippi, Alabama and Florida, and age was estimated from sagittal otoliths. Stomachs from some specimens were retained for dietary analyses. Age classes spanned 0–20 years. Overall growth was best represented by the logistic growth model, whereas sex‐specific growth was best represented by a version of the von Bertalanffy growth function that allowed L ∞ to vary by sex while holding k and t 0 constant between sexes. Fishes were more important to crevalle jack diet than invertebrates, and diet varied among locations and years. These findings will address fundamental knowledge gaps to inform age‐based stock assessments for crevalle jack and ecosystem approaches to fisheries management in the Gulf of Mexico.

Summer ecosystem structure in mountain lakes linked to interannual variability of lake ice, snowpack, and landscape attributes - Stephen M. Powers; Steven C. Fradkin; William Baccus; Carmen Archambault; John R. Boetsch; Matthew R. Brousil; Rebecca Lofgren; Ashley Rawhouser; Stephanie E. Hampton (Limnology and Oceanography, 2022)
Mountain lakes experience interannual variability in spring snowpack and ice cover that can lead to differences in physical, chemical, and biological properties in the succeeding summer. Lake studies that capture extreme years of snow and ice would be useful to understand and anticipate effects of climate change, but such data are rare for remote mountain lakes. Monitoring of lakes in Olympic, North Cascades, and Mount Rainier National Parks from 2007 to 2018 allowed us to examine limnological differences along interannual and elevation‐driven climate gradients that included unusually high (2011–2012) and 100‐yr record low (2015) snowpack years. Years with lower spring snowpack had earlier ice‐out. Across lakes, our analysis suggested an average of 0.075°C lake warming per day of lost ice duration (0.525°C per week), giving rise to other ecosystem changes linked to temperature such as lower dissolved oxygen, higher total dissolved N, higher chlorophyll, and higher abundance of cladoceran zooplankton. Conversely, in years with higher snowpack and a shorter ice‐free season, lakes were colder and clearer (1 m deeper Secchi depth for every 1 m May snow water equivalent), with more dilute ions as well as lower algal biomass and zooplankton abundance. These results add to evidence that changes in snowpack or ice‐out dates alter mountain lake ecology through multiple processes associated with hydrology, terrestrial‐aquatic connection, water temperature, productivity, ion composition, and plankton communities.

Strategies to acquire and use phosphorus in phosphorus-impoverished and fire-prone environments - Hans Lambers; Patrícia de Britto Costa; Gregory R. Cawthray; Matthew D. Denton; Patrick M. Finnegan; Patrick E. Hayes; Rafael S. Oliveira; Simon C. Power; Kosala Ranathunge; Qi Shen; Xiao Wang; Hongtao Zhong (Plant and Soil, 2022)
Background Unveiling the diversity of plant strategies to acquire and use phosphorus (P) is crucial to understand factors promoting their coexistence in hyperdiverse P-impoverished communities within fire-prone landscapes such as in cerrado (South America), fynbos (South Africa) and kwongan (Australia). Scope We explore the diversity of P-acquisition strategies, highlighting one that has received little attention: acquisition of P following fires that temporarily enrich soil with P. This strategy is expressed by fire ephemerals as well as fast-resprouting perennial shrubs. A plant’s leaf manganese concentration ([Mn]) provides significant clues on P-acquisition strategies. High leaf [Mn] indicates carboxylate-releasing P-acquisition strategies, but other exudates may play the same role as carboxylates in P acquisition. Intermediate leaf [Mn] suggests facilitation of P acquisition by P-mobilising neighbours, through release of carboxylates or functionally similar compounds. Very low leaf [Mn] indicates that carboxylates play no immediate role in P acquisition. Release of phosphatases also represents a P-mining strategy, mobilising organic P. Some species may express multiple strategies, depending on time since germination or since fire, or on position in the landscape. In severely P-impoverished landscapes, photosynthetic P-use efficiency converges among species. Efficient species exhibit rapid rates of photosynthesis at low leaf P concentrations. A high P-remobilisation efficiency from senescing organs is another way to use P efficiently, as is extended longevity of plant organs. Conclusions Many P-acquisition strategies coexist in P-impoverished landscapes, but P-use strategies tend to converge. Common strategies of which we know little are those expressed by ephemeral or perennial species that are the first to respond after a fire. We surmise that carboxylate-releasing P-mobilising strategies are far more widespread than envisaged so far, and likely expressed by species that accumulate metals, exemplified by Mn, metalloids, such as selenium, fluorine, in the form of fluoroacetate, or silicon. Some carboxylate-releasing strategies are likely important to consider when restoring sites in biodiverse regions as well as in cropping systems on P-impoverished or strongly P-sorbing soils, because some species may only be able to establish themselves next to neighbours that mobilise P.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

From quartz curvature to late Holocene mobility at Spring Cave, Western Cape, South Africa - Benjamin Davies; Matthew J. Douglass; David R. Braun; John Parkington; Mitchell J. Power; J. Tyler Faith (Archaeological and Anthropological Sciences, 2022)

The 16th Workshop on Antarctic Meteorology and Climate and 6th Year of Polar Prediction in the Southern Hemisphere Meeting - David H. Bromwich; Matthew A. Lazzara; Arthur M. Cayette; Jordan G. Powers; Kirstin Werner; John J. Cassano; Steven R. Colwell; Scott Carpentier; Xun Zou (Advances in Atmospheric Sciences, 2022)

The clinical presentation, treatment and outcome of serologically confirmed paediatric Lyme disease in the Republic of Ireland over a 5-year period: a retrospective cohort study - Karina M. Forde; Joanne O’Gorman; Patrick J. Gavin; Matthew S. Dryden; Deirbhile Keady; Belinda Hanahoe; Colm McDonnell; Lorraine Power; Bartley Cryan; James Sweeney; Karl F. Conyard; Michael J. O’Grady (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Ecometrics and the paleoecological implications of Pleistocene faunas from the western coastal plains of the Cape Floristic Region, South Africa - J. Tyler Faith; David R. Braun; Benjamin Davies; Larisa R. G. DeSantis; Matthew J. Douglass; Irene Esteban; Vincent Hare; Naomi E. Levin; Julie Luyt; Robyn Pickering; Mitchell J. Power; Judith Sealy; et al. (Journal of Quaternary Science, 2020)
The Pleistocene ungulate communities from the western coastal plains of South Africa's Cape Floristic Region (CFR) are diverse and dominated by grazers, in contrast to the region's Holocene and historical faunas, which are relatively species‐poor and dominated by small‐bodied browsers and mixed feeders. An expansion of grassy habitats is clearly implied by the Pleistocene faunas, but the presence of ruminant grazers that cannot survive the summer dry season typical of the region today suggests other important paleoecological changes. Here we use dental ecometrics to explore the paleoecological implications of the region's Pleistocene faunas. We show that the dental traits (hypsodonty and occlusal topography) of the ungulates that occurred historically in the CFR track annual and summer aridity, and we use these relationships to reconstruct past aridity. Our results indicate that the Pleistocene faunas signal paleoenvironments that were on average less arid than today, including during the summer, consistent with other lines of evidence that suggest a higher water table and expansion of well‐watered habitats. Greater water availability can be explained by lower temperature and reduced evapotranspiration during cooler phases of the Pleistocene, probably coupled with enhanced groundwater recharge due to increased winter precipitation.

Predicting adult lifespan and lifetime reproductive success from early-life reproductive events - Matthew J. Powers; Ryan J. Weaver; Kyle B. Heine; Geoffrey E. Hill (Marine Biology, 2020)

The 13th and 14th Workshops on Antarctic Meteorology and Climate - Matthew A. Lazzara; Sophie A. Orendorf; Taylor P. Norton; Jordan G. Powers; David H. Bromwich; Scott Carpentier; John J. Cassano; Steven R. Colwell; Arthur M. Cayette; Kirstin Werner (Advances in Atmospheric Sciences, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Arctic shrub colonization lagged peak postglacial warmth: Molecular evidence in lake sediment from Arctic Canada - Sarah E. Crump; Gifford H. Miller; Matthew Power; Julio Sepúlveda; Nadia Dildar; Megan Coghlan; Michael Bunce (Global Change Biology, 2019)
Arctic shrubification is an observable consequence of climate change, already resulting in ecological shifts and global‐scale climate feedbacks including changes in land surface albedo and enhanced evapotranspiration. However, the rate at which shrubs can colonize previously glaciated terrain in a warming world is largely unknown. Reconstructions of past vegetation dynamics in conjunction with climate records can provide critical insights into shrubification rates and controls on plant migration, but paleoenvironmental reconstructions based on pollen may be biased by the influx of exotic pollen to tundra settings. Here, we reconstruct past plant communities using sedimentary ancient DNA ( sed aDNA), which has a more local source area than pollen. We additionally reconstruct past temperature variability using bacterial cell membrane lipids (branched glycerol dialkyl glycerol tetraethers) and an aquatic productivity indicator (biogenic silica) to evaluate the relative timing of postglacial ecological and climate changes at a lake on southern Baffin Island, Arctic Canada. The sed aDNA record tightly constrains the colonization of dwarf birch ( Betula , a thermophilous shrub) to 5.9 ± 0.1 ka, ~3 ka after local deglaciation as determined by cosmogenic 10 Be moraine dating and >2 ka later than Betula pollen is recorded in nearby lake sediment. We then assess the paleovegetation history within the context of summer temperature and find that paleotemperatures were highest prior to 6.3 ka, followed by cooling in the centuries preceding Betula establishment. Together, these molecular proxies reveal that Betula colonization lagged peak summer temperatures, suggesting that inefficient dispersal, rather than climate, may have limited Arctic shrub migration in this region. In addition, these data suggest that pollen‐based climate reconstructions from high latitudes, which rely heavily on the presence and abundance of pollen from thermophilous taxa like Betula , can be compromised by both exotic pollen fluxes and vegetation migration lags.

A framework to measure the wildness of managed large vertebrate populations - Matthew F. Child; S. A. Jeanetta Selier; Frans G. T. Radloff; W. Andrew Taylor; Michael Hoffmann; Lizanne Nel; R. John Power; Coral Birss; Nicola C. Okes; Michael J. Peel; David Mallon; Harriet Davies‐Mostert (Conservation Biology, 2019)
As landscapes continue to fall under human influence through habitat loss and fragmentation, fencing is increasingly being used to mitigate anthropogenic threats and enhance the commercial value of wildlife. Subsequent intensification of management potentially erodes wildness by disembodying populations from landscape‐level processes, thereby disconnecting species from natural selection. Tools are needed to measure the degree to which populations of large vertebrate species in formally protected and privately owned wildlife areas are self‐sustaining and free to adapt. We devised a framework to measure such wildness based on 6 attributes relating to the evolutionary and ecological dynamics of vertebrates (space, disease and parasite resistance, exposure to predation, exposure to limitations and fluctuations of food and water supply, and reproduction). For each attribute, we set empirical, species‐specific thresholds between 5 wildness states based on quantifiable management interventions. We analysed data from 205 private wildlife properties with management objectives spanning ecotourism to consumptive utilization to test the framework on 6 herbivore species representing a range of conservation statuses and commercial values. Wildness scores among species differed significantly, and the proportion of populations identified as wild ranged from 12% to 84%, which indicates the tool detected site‐scale differences both among populations of different species and populations of the same species under different management regimes. By quantifying wildness, this framework provides practitioners with standardized measurement units that link biodiversity with the sustainable use of wildlife. Applications include informing species management plans at local scales; standardizing the inclusion of managed populations in red‐list assessments; and providing a platform for certification and regulation of wildlife‐based economies. Applying this framework may help embed wildness as a normative value in policy and mitigate the shifting baseline of what it means to truly conserve a species.

The 12th Workshop on Antarctic Meteorology and Climate - Matthew A. Lazzara; Jordan G. Powers; Carol A. Costanza; David H. Bromwich; Scott Carpentier; Steve R. Colwell (Advances in Atmospheric Sciences, 2018)

A Meta-analysis of Arsenic Exposure and Lung Function: Is There Evidence of Restrictive or Obstructive Lung Disease? - Tiffany R. Sanchez; Martha Powers; Matthew Perzanowski; Christine M. George; Joseph H. Graziano; Ana Navas-Acien (Current Environmental Health Reports, 2018)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Seasonality and Ontogenetic Habitat Partitioning of Cownose Rays in the Northern Gulf of Mexico - Matthew J. Ajemian; Sean P. Powers (Estuaries and Coasts, 2016)

The 10th Antarctic meteorological observation, modeling, and forecasting workshop - Steve R. Colwell; Arthur M. Cayette; Matthew A. Lazzara; Jordan G. Powers; David H. Bromwich; John J. Cassano; Scott Carpentier (Advances in Atmospheric Sciences, 2016)

Fish community dynamics following dam removal in a fragmented agricultural stream - Matthew S. Kornis; Brian C. Weidel; Stephen M. Powers; Matthew W. Diebel; Timothy J. Cline; Justin M. Fox; James F. Kitchell (Aquatic Sciences, 2015)

Towed-float satellite telemetry tracks large-scale movement and habitat connectivity of myliobatid stingrays - Matthew J. Ajemian; Sean P. Powers (Environmental Biology of Fishes, 2014)

Habitat-specific feeding by cownose rays (Rhinoptera bonasus) of the northern Gulf of Mexico - Matthew Joseph Ajemian; Sean Paul Powers (Environmental Biology of Fishes, 2012)

Effects of the novel endocannabinoid uptake inhibitor, LY2183240, on fear-potentiated startle and alcohol-seeking behaviors in mice selectively bred for high alcohol preference - Matthew S. Powers; Gustavo D. Barrenha; Nate S. Mlinac; Eric L. Barker; Julia A. Chester (Psychopharmacology, 2010)

Ungulate Carcasses Perforate Ecological Filters and Create Biogeochemical Hotspots in Forest Herbaceous Layers Allowing Trees a Competitive Advantage - Joseph K. Bump; Christopher R. Webster; John A. Vucetich; Rolf O. Peterson; Joshua M. Shields; Matthew D. Powers (Ecosystems, 2009)

UNINTENDED FACILITATION BETWEEN MARINE CONSUMERS GENERATES ENHANCED MORTALITY FOR THEIR SHARED PREY - F. Joel Fodrie; Matthew D. Kenworthy; Sean P. Powers (Ecology, 2008)
We manipulated predator densities and prey vulnerability to explore how interactions between two predators affect overall mortality of their shared prey. Our three‐member study system included eastern oysters ( Crassostrea virginica ) and two of its major consumers: southern oyster drills ( Stramonita haemastoma ) and stone crabs ( Menippe adina ). Field experiments demonstrated that drills and crabs foraging together generated higher than expected oyster mortality based on each species operating independently, even though crabs also killed some drills. In subsequent laboratory trials, we experimentally mimicked the handling of oysters by foraging crabs and confirmed that crabs facilitated drills by breeching oyster valves, thereby granting easy access for drills to their prey. Facilitation between co‐occurring predators is uncommon and typically occurs because the behavior or habitat selection of a prey species is altered by the presence of one predator, consequently making the prey more susceptible to another predator. Whereas oysters are sedentary regardless of the predator field, we observed an entirely different mechanism that resulted in predator facilitation. This involved direct attacks on the physical defenses of oysters by one predator that ultimately increased the overall consumption rate of foraging species. These dynamics significantly enhanced mortality risk for a foundation species within an estuarine ecosystem.

Stoichiometry of soil enzyme activity at global scale - Robert L. Sinsabaugh; Christian L. Lauber; Michael N. Weintraub; Bony Ahmed; Steven D. Allison; Chelsea Crenshaw; Alexandra R. Contosta; Daniela Cusack; Serita Frey; Marcy E. Gallo; Tracy B. Gartner; Sarah E. Hobbie; et al. (Ecology Letters, 2008)
Extracellular enzymes are the proximate agents of organic matter decomposition and measures of these activities can be used as indicators of microbial nutrient demand. We conducted a global‐scale meta‐analysis of the seven‐most widely measured soil enzyme activities, using data from 40 ecosystems. The activities of β‐1,4‐glucosidase, cellobiohydrolase, β‐1,4‐ N ‐acetylglucosaminidase and phosphatase g −1 soil increased with organic matter concentration; leucine aminopeptidase, phenol oxidase and peroxidase activities showed no relationship. All activities were significantly related to soil pH. Specific activities, i.e. activity g −1 soil organic matter, also varied in relation to soil pH for all enzymes. Relationships with mean annual temperature (MAT) and precipitation (MAP) were generally weak. For hydrolases, ratios of specific C, N and P acquisition activities converged on 1 : 1 : 1 but across ecosystems, the ratio of C : P acquisition was inversely related to MAP and MAT while the ratio of C : N acquisition increased with MAP. Oxidative activities were more variable than hydrolytic activities and increased with soil pH. Our analyses indicate that the enzymatic potential for hydrolyzing the labile components of soil organic matter is tied to substrate availability, soil pH and the stoichiometry of microbial nutrient demand. The enzymatic potential for oxidizing the recalcitrant fractions of soil organic material, which is a proximate control on soil organic matter accumulation, is most strongly related to soil pH. These trends provide insight into the biogeochemical processes that create global patterns in ecological stoichiometry and organic matter storage.

13C labeling of plant assimilates using a simple canopy-scale open air system - Alan F. Talhelm; Samir A. Qadir; Matthew D. Powers; Kate L. Bradley; Alexander L. Friend; Kurt S. Pregitzer (Plant and Soil, 2007)

Agrobacterium-mediated transformation of Lupinus mutabilis L. using shoot apical explants - Mehmet Babaoglu; Matthew S. McCabe; J. Brian Power; Michael R. Davey (Acta Physiologiae Plantarum, 2000)

Expression of the Bar Gene Confers Herbicide Resistance in Transgenic Lettuce - Umaballava Mohapatra; Matthew S. McCabe; J. Brian Power; Frank Schepers; Aad Van Der Arend; Michael R. Davey (Transgenic Research, 1999)

DNA Isolation and AFLP™ Genetic Fingerprinting of shape Theobroma cacao (L.) - Matthew D. Perry; Michael R. Davey; J. Brian Power; Kenneth C. Lowe; H. Frances J. Bligh; Paul S. Roach; Chris Jones (Plant Molecular Biology Reporter, 1998)